PERANAN ETIKA PROFESI DALAM PERILAKU AKUNTAN - Mispiyanti Mispiyanti (P4M STIE Putra Bangsa, 2016)
The aim of the research is to present the development of behavioral accounting research related to the ethical individuals who manage information. The research is literature review from the results of of the research done by other researchers. The research result showed each individual in the execution of professional duties should consider the ethics of professions such as in the use of authority ownership, establish connections with politicians, character building manager, and in the preparation of the company's budget. Professional ethics is very important to be applied in order to support the implementation of behavioral accounting that may affect the smooth operation of the company both on the policy side or the other. Key Words : Accounting Behavioral, Professional ethics, Possession, Character